STUDY ON INFLUENCING FACTORS TO THE CYLINDER LINER PRE-TIGHTENING DEFORMATION OF TURBOCHARGED INTER-COOLED DIESEL ENGINE - XIANG Rong; BI YuHua; LEI JiLin; SONG GuoFu; SHEN LiZhong; XU YuanZhi (Jixie qiangdu)
In this paper,the cylinder body-cylinder head-cylinder liner assembly coupled model is established based on the theory of elasticity and the method of contact. The cylinder liner deformation characteristics and the factors causing the deformation are studied under the preloaded cases. The results show that the four liners deformation is uneven and the first and the fourth cylinder liner are larger than the second and the third cylinder liner deformation. After optimizing the cylinder block,the cylinder liners radial distortion and deformation have decreased. With the bolt preload forces increasing,the cylinder liners deformation has increased. The closer cylinder head bolt counter bore depth is to the height of the cylinder convex shoulder,the greater the liners deformation is. When the cylinder convex shoulder angle is set to 20’,the liners deformation is relatively small.The length of action of cylinder head bolts has less influence on the radial deformation of cylinder liners.